Hepatic Tuberculosis of Pseudotumor Form - Sabbah, Meriam; Bibani, Norsaf; Trad, Dorra; Ouakaa, Asma; Elloumi, Hela; Gargouri, Dalila; Lahmar, Ahlem; Kharrat, Jamel (Journal of Spleen And Liver Research, 2018)
Tuberculosis involving the liver in the absence of active pulmonary tuberculosis is very rare. The inflammatory pseudotumoral form is an entity difficult to diagnose. We report a case of an inflammatory pseudotumor of the liver due to tuberculosis, who didn’t underwent hepatectomy because of the size of the tumor. The diagnosis of tuberculosis was made on biopsy and Polymerase Chain Reaction (PCR).